Cement Embolism following Vertebroplasty: a case report - Siniscalchi, Carmine; Epifani, Enrico; Basaglia, Manuela (Acta Biomedica Atenei Parmensis, 2022)
Vertebroplasty consists of injection under image guidance of a cement polymer, commonly polymethylmethacrylate, into the vertebral body to improved stability. Vertebroplasty is essentially safety. However whether vertebral compression or (micro)fractures occur during the procedure, the high vascularization and the anatomic network of the paravertebral and extradural venous plexuses, can facilitate migration of cement fragments into the systemic venous circulation. We described the case of cement pulmonary embolism in a 75-year-old-female after vertebloplasty. A chest CT scan showed a multiple and spontaneus hyperdensities suggesting cement pulmonary-emboli. There are different therapeutic approach depending of the clinical severity. For asymptomatic patients clinical surveillance or prophylactic LMWH. Active treatment has been suggested only for symptomatic cases.